2008
DOI: 10.1016/j.anbehav.2006.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Animal economics: assessing the motivation of female laboratory rabbits to reach a platform, social contact and food

Abstract: We used novel techniques for assessing resource value to investigate what additions to a barren cage female laboratory rabbits, Oryctolagus cuniculus, value. We tested motivation to reach two resources that are potentially practical enrichments: a platform (providing a partly enclosed space and a raised area) and limited social contact with another rabbit through wire mesh and compared these to food and an empty space. To reach these resources, rabbits had to pay entry costs (pushing through weighted doors) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…As described by Seaman et al (2008), rearing can be considered an exploratory or alert behaviour, and both of them are activities which may increase when animals are in a novel environment. Thus, rearing can be observed when rabbits are subjected to an open field test (Verwer et al, 2009;Hansen and Berthelsen, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…As described by Seaman et al (2008), rearing can be considered an exploratory or alert behaviour, and both of them are activities which may increase when animals are in a novel environment. Thus, rearing can be observed when rabbits are subjected to an open field test (Verwer et al, 2009;Hansen and Berthelsen, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Held et al (1995) found that low-ranking rabbits do not necessarily prefer a solitary compartment to a group pen. In an experimental setting, rabbits work equally hard to reach social contact as for food (Seaman et al, 2008). Although rabbits may prefer group life to single life, the need to maintain differentiated relationships, and the need to avoid interactions by maintaining inter-individual distances, should be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…However, as with primates, the evidence supporting the benefit of socially housing rabbits cannot be ignored. Studies have demonstrated that socially housed rabbits are less likely to engage in a number of abnormal behaviors (Held et al, 2001) and will work as hard for social contact as for food (Seaman et al, 2008). Additionally, several papers have been published describing the mechanics of successfully introducing and maintaining groups of rabbits, including castrated males (Love, 1994;Raje and Stewart, 1997).…”
Section: Consideration 1: Why Is Refinement Important?mentioning
confidence: 99%